Problems of improving the effectiveness of organizational management activities of leaders of the professional education system (Eurasian Scientific Herald, 2022)
In this article it is written about institutional leaders in vocational education and training (VET) refer to those who are appointed or employed in a recognised leadership position to oversee VET programmes and institutions and who have responsibility for the goals set by the organisation that offers VET programmes.